Metaphor as Will-generated Cognition: A Philosophical Analysis - Sangeeta Tushir (Innovative Research Thoughts, 2023)
Reviewing the point of view of NavyaNyāya Philosophy, we see that there is also a cognitive aspect to desire something. Such intentional desire is found not only in Navya Nyaya but in addition to this in other traditional treatises like Grammar, Alam᷾ ka̅rsa͆stra, Bhațțikavya͆ etc. In Indian literature metaphors (ru̅paka) are used in poetry, literature and anytime when someone wants to add some colour to their language. In metaphor, a person is compared to an object which is not same with him but having some resemblances. Keywords: traditional, desire, language, literature, person.